Evaluation of copper nanoparticles and copper sulfate effect on immune status, behavior, and productive performance of broilers (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study was conducted to compare between the nanoparticles of copper (Cu-NP) and copper sulfate (CuSO4) effect on immunity, pro-inflammatory cytokine, oxidant/antioxidant balance, different behavioral patterns, growth rate, and weight gain by adding them in drinking water of broilers.Materials and Methods: One hundred and fifty broiler chicks of 1-day-old were randomly divided into three groups: the first group was the control, the second group received CuSO4 in drinking water (10 mg/l), and the third group received Cu-NP in drinking water (10 mg/l) with replicates (n = 25) for 5 weeks of age. Blood samples collected for estimating immunoglobulins (A, G, and M), superoxide dismutase, pro-inflammatory (IL-6), erythrocyte sedimentation rate, heterophil/ lymphocyte (H/L) ratio, malondialdehyde (MDA), corticosterone hormone, and lymphoid organs index weight. Moreover, behavioral observations were undertaken from the 2nd week until the 5th week of age for measuring different behavioral patterns (feeding, drinking, crouching, body care, and comfort behaviors). Chicks were individually weighed weekly (gm); also, the weight gain, the intake of food, and the ratio of feed conversion were calculated.Results: Cu-NP administration has improved the blood profile, lymphoid organs index weight in Cu-NP treated broilers in relation to control and CuSO4 treated groups. Conversely, erythrocyte sedimentation rate, H/L ratio, MDA, and corticosterone hormone were reduced by Cu-NP treatment. Moreover, Cu-NP has a positive effect on all behavioral patterns more than other groups which significantly reflect on the weight of the body, gaining of weight, and the intake of food in the Cu-NP treated group of birds.Conclusion: The findings in this study stated that when the drinking water of broilers was supplemented with Cu-NP, there might be an improvement in the immunity, behavior, and productive performance more efficiently than CuSO4.J. Adv. Vet. Anim. Res., 7(1): 16-25, March 2020